Activated Carbon as Superadsorbent and Sustainable Material for Diverse Applications. (24th March 2022) - Sharma, Gaurav; Sharma, Shweta; Kumar, Amit; Lai, Chin Wei; Naushad, Mu.; Shehnaz; Iqbal, Jibran; Stadler, Florian J.
Abstract : Activated carbon is a carbonaceous material with highly porous structure. Different functionalities can be introduced to its surface by various physical and chemical treatments. Various precursors can be used for the synthesis of activated carbon such as fossil fuels, agricultural wastes, and lignocellulosic wastes, etc. Number of papers have been reported in literature devoted to the synthesis, characterization, and various applications of activated carbon. Herein, in this review, special attention has been paid to the basic properties of activated carbon and its surface chemistry originated due to physical and chemical treatment. In addition, a general introduction to adsorption process, various adsorption isotherms, and adsorption kinetics is also included. A brief description of mechanism of adsorption onto activated carbon is also presented. At last, most probable applications of activated carbon such as adsorption of pollutants (e.g., dyes, heavy metal ions, pesticides, pharmaceutical waste products, and volatile organic organic), as catalyst support, anduse in food and pharmaceutical industries is also presented.